2020
DOI: 10.47626/1679-4435-2020-582
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease and associated risk factors in health care professionals in a community hospital in Brazil

Abstract: Introduction: Health care professionals are vulnerable to several health problems, including overweight, stress and anxiety. As such, non-alcoholic fatty liver disease is a likely diagnosis in this population. Objectives: To investigate the association between non-alcoholic fatty liver disease and levels of stress and anxiety in a sample of health care workers in a community hospital in the state of Rio Grande do Sul. Methods: The sample cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…For the 31 studies included in this systematic review, NAFLD was defined by various means including liver biopsy, ultrasonography/evidence of ultrasound, hepatic steatosis index, pathology and/or radiologic testing, computed tomography, magnetic resonance imaging, and self-reported physician diagnosis ( Table 1 ). From the 31 included studies, 18 studies (58%) measured only depression ( 44 , 49 53 , 57 , 58 , 61 70 ), one study measured only anxiety ( 55 ), 10 studies (32%) measured depression and anxiety ( 43 , 45 48 , 56 , 60 , 71 73 ), one study measured only stress ( 54 ), and one study measured stress and anxiety ( 59 ). In these studies, the mental health conditions of interest were identified by validated measures (including DSM-IV and ICD-10) in 17 studies ( 44 , 46 , 48 , 49 , 53 , 54 , 56 59 , 63 , 65 – 68 , 70 , 73 ), self-reported in six studies ( 43 , 47 , 55 , 61 , 62 , 69 ), or identified by other diagnosis (e.g., medical history) in eight studies ( 45 , 50 52 , 60 , 64 , 71 , 72 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For the 31 studies included in this systematic review, NAFLD was defined by various means including liver biopsy, ultrasonography/evidence of ultrasound, hepatic steatosis index, pathology and/or radiologic testing, computed tomography, magnetic resonance imaging, and self-reported physician diagnosis ( Table 1 ). From the 31 included studies, 18 studies (58%) measured only depression ( 44 , 49 53 , 57 , 58 , 61 70 ), one study measured only anxiety ( 55 ), 10 studies (32%) measured depression and anxiety ( 43 , 45 48 , 56 , 60 , 71 73 ), one study measured only stress ( 54 ), and one study measured stress and anxiety ( 59 ). In these studies, the mental health conditions of interest were identified by validated measures (including DSM-IV and ICD-10) in 17 studies ( 44 , 46 , 48 , 49 , 53 , 54 , 56 59 , 63 , 65 – 68 , 70 , 73 ), self-reported in six studies ( 43 , 47 , 55 , 61 , 62 , 69 ), or identified by other diagnosis (e.g., medical history) in eight studies ( 45 , 50 52 , 60 , 64 , 71 , 72 ).…”
Section: Resultsmentioning
confidence: 99%
“…From the 31 included studies, 18 studies (58%) measured only depression ( 44 , 49 53 , 57 , 58 , 61 70 ), one study measured only anxiety ( 55 ), 10 studies (32%) measured depression and anxiety ( 43 , 45 48 , 56 , 60 , 71 73 ), one study measured only stress ( 54 ), and one study measured stress and anxiety ( 59 ). In these studies, the mental health conditions of interest were identified by validated measures (including DSM-IV and ICD-10) in 17 studies ( 44 , 46 , 48 , 49 , 53 , 54 , 56 59 , 63 , 65 – 68 , 70 , 73 ), self-reported in six studies ( 43 , 47 , 55 , 61 , 62 , 69 ), or identified by other diagnosis (e.g., medical history) in eight studies ( 45 , 50 52 , 60 , 64 , 71 , 72 ). Characteristics of the included studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations